Persistent legal disagreement: its nature and theoretical relevance - Torres, Ismael Martínez (The University of Edinburgh, 2022)
Disagreement among legal practitioners (mainly, judges and lawyers) about the content of the law is a pervasive feature of any modern legal system. Sometimes, subjects disagree about the content of the law because they disagree over some non-legal issues (e.g., empirical facts, linguistic facts, rules of logic, etc.). For instance, two people in California may disagree over whether the speed limit is 55 miles an hour because they disagree over whether the relevant statute contains a provision to that effect. Some other times, subjects disagree about the content of the law despite their agreement over every other (relevant) non-legal issue. For example, two judges may disagree over whether an inheritor who murdered her testator is entitled to the inheritance despite there being agreement between them (the judges) over the fact that the inheritor did kill the testator, the fact that there was a valid will in which the murderer figured as the heir, etc. I label the latter type of disagreement ‘persistent legal disagreement’ (PLD). Some legal philosophers have taken PLD to be theoretically significant. They have suggested that looking at PLD may be helpful to explain some features of law, legal practice, and legal discourse. More spe-cifically, some legal philosophers have advanced disagreement-based arguments (i.e. arguments that draw on some observations about PLD) to support their views about the nature of law, legal practice and legal discourse. This thesis is an analysis of PLD and its role in argumentation within philosophy of law. In this thesis, I pursue five aims. First, I aim to provide a complete description of PLD. The de-scription is complete in the sense that it accounts for the structural and substantive features of this type of disagreement. Second, I aim to show that most (if not all) disagreement-based arguments in legal philosophy are committed to a particular understanding of PLD. I call this standard under-standing ‘the content view’. According to the content view, disagreement is a relation that obtains between two propositional attitudes when their contents are incompatible. Third, I aim to show that this way of thinking about PLD is mistaken. I argue that PLD cannot be understood as a relation between the contents of propositional attitudes. Fourth, I aim to propose an alternative account of PLD. I call this alternative account the functionalist view. According to the functionalist view, disa-greement is a relation that is sensitive to the functions of attitudes. Finally, I aim to make explicit how, when we drop the content view and adopt the functionalist view, most (if not all) arguments that have been suggested in legal philosophy that are premised on observations about PLD fail to deliver their conclusions. This thesis proceeds as follows. In chapter one, I suggest a description of the structure of PLD. According to this description, PLD involves two disagreements (one over the content of the law and one that concerns the concept THE CRITERIA OF LEGAL VALIDITY) and an explanatory rela-tion between them. The description of PLD suggested in this chapter is not committed to any sub-stantive account of what the relation of disagreement is or what type of attitudes constitute PLD. In chapter two, I present the content view and argue that such a conception of disagreement is mistaken. My argument is that incompatibility between contents is neither sufficient nor neces-sary for disagreement. Additionally, I introduce an alternative conception of PLD: the functionalist view. As mentioned, according to the functionalist view, disagreement is a relation that is sensitive to the functions of attitudes. In chapter three, I tackle the question of what type of attitudes are involved by PLD. I argue against the view that PLD involves two non-cognitive attitudes. I contend instead that PLD in-volves two cognitive attitudes. My argument is premised on two observations. Firstly, I argue that if PLD involved non-cognitive attitudes, then it would be faultless; secondly, I argue that PLD is not faultless. In chapter four, I examine the disagreement that concerns the concept THE CRITERIA OF LEGAL VALIDITY in PLD. I clarify the claim, common in legal philosophy, that disagreement re-quires some sort of coordination between subjects. Contrary to the standard view, I argue that two people can coordinate and thus disagree despite not having the same concepts. My arguments rely on recent developments suggested by cognitive scientists. In chapter five, I pursuit a twofold goal. On the one hand, I aim to make explicit that three important disagreement-based arguments in legal philosophy entail the content view. Those argu-ments are: Dworkin’s argument against legal positivism, Kevin Toh’s argument for legal expres-sivist, and David Plunkett and Timothy Sundell’s analysis of the disputes they call bedrock legal disputes. On the other hand, I aim to make explicit the way in which once we replace the content view with the functionalist view, those arguments fail to deliver their conclusions.
Keywords: Persistent Disagreement; Dworkin; Philosophy of Law; Disagreement